Sydney Cambodian Music Ensemble recorded by Peter Parkhill for the Peter Parkhill collection - Sydney Cambodian Music Ensemble; Parkhill, Peter (1988)
Folkloric recording.
Recorded in January 1988, at Fairfield, N.S.W.
Digital master available
Keywords: Sydney Cambodian Music Ensemble; Cambodians -- New South Wales -- Sydney; Folk music -- Cambodia